La interdependencia económica y cultural de Texas y México: el caso del chili con carne - Margarita Calleja Pinedo (Caravelle, 2011)
The territory that is now the State of Texas is the product of a fusion of the various life styles of the native, European and Mexican populations that have lived there, adapting it and transforming it through conquests, waves of immigration, armed conflicts and political agreements. The aim of the present work is to address this fusion of different ways of life from a cultural point of view, and in particular the culinary symbiosis of the region referred to as Tex-Mex cuisine, which is distinct from the Mexican and United States traditions it derives from, and has been nourished by the socio-economic and cultural interdependence of Mexico and the United States since the nineteenth century.